Bukan Kameo: Roh Kudus sebagai Arche Trinitas menjadi Basis Kesetaraan Gender bagi Perempuan dalam Narasi Misi - Harefa, Oinike (STFT Jakarta, Indonesia, 2024)
The role of the Holy Spirit is often seen as “complementary” in the Trinitarian relationship. Likewise, the role of women in mission narratives is also often seen as complementary. This study aims to elaborate on the concept of the Holy Spirit in the Trinitarian arche as the basis for gender equality for women in mission narratives. For this purpose, I reclaim the primacy of the role of the Holy Spirit in the Trinitarian arche as the basis for gender equality. Furthermore, I discuss several women’s mission theories to be analyzed based on a feminist perspective, specifically gender analysis. In the final part, I highlight the narrative of women on mission as the work of the Holy Spirit on mission history. I specifically delve into missionary women in the Nias context.